Realism in the Kiarostami’s Films - Oveisi, Kaveh (Opción, 2019)
In this article, we will look at the concept of realism in Kiarostami films and in this way, we will determine the type of realism of his works via comparative qualitative research method. As a result, a theoretical framework that evaluates the evolution of Kiarostami's cinematic realism is not a closed form but like contemporary thought, it is an open mind whose components relies on modern ontology, anti-determinism, with abandonment of the great frameworks of the dogma's ideological narratives. In conclusion, Kiarostami’s cinema in our contemporary world has a postmodern and mini-realistic perception of a questionable realism and has been foundational.